INTERNALIZATION OF MAPALUS LOCAL WISDOM IN PUBLIC HIGHER EDUCATION BUREAUCRACY: A STUDY ON UNIMA EDUCATIONAL PERSONNEL - Kansil, Fabiola Tirsa; Sumaryana, Asep; Utami, Sawitri Budi (International Journal of Cultural and Social Science, 2026)
In the discipline of Public Administration, which increasingly acknowledges the crucial role of local wisdom in building responsive governance, this research aims to investigate the process of internalizing the local wisdom value of Mapalus among academic staff at Manado State University, a public higher education institution, with implication for public organizational governance. Using qualitative approach, this study analyzes value communication, cultural understanding, and reinforcemenet mechanisms within the bureaucratic context, through in-depth interviews, observation, and document studies. The findings indicate that Mapalus internalization is strongly supported by cultural foundations and leadership legitimacy, but value communication is informal, and reinforcement mechanisms are dominated by civil servant discipline and external incentives rather than specific Mapalus values. Consequently, Mapalus exist as a personal social ethos but has not been fully institutionally embedded in UNIMA’s work system. This study implies the importance of developing an adaptive value internalization framework for human resources policies and public bureaucratic cultural reforms strategies.